ZIARAH ROHANI DAN PEMBENTUKAN KARAKTER RELIGIUS SISWA - Rosalia Ita; Martinus Martinus; Hemma Gregorius Tinenti (STP Reinha Larantuka, 2026)
This study aims to describe the religious character of sixth-grade students and explore their perceptions, along with those of the Catholic Religion teacher, regarding the role of spiritual pilgrimage activities in the development of religious character at SD Negeri 08 Cupang Gading, Sekadau Hulu. This research employed a qualitative approach through observation, documentation, and in-depth interviews. The findings indicate that students demonstrate good religious character, as seen in their habits of praying before and after class, showing respect to teachers, and actively participating in religious education lessons. The spiritual pilgrimage activity provides a meaningful religious experience that reinforces students' spiritual values. Students reported feeling happy, peaceful, and inspired through shared prayers, scripture reflection, and interaction with nature and peers. Teachers affirmed that the pilgrimage effectively shapes religious values through contextual and experiential learning. These results support theories of experiential learning and character education, which emphasize that direct experiences significantly influence the formation of students’ values and attitudes. Therefore, spiritual pilgrimage activities are recommended as a strategic component in developing religious character in primary school education.